The effects of ludic activities as a motivational strategy to evolve oral production of intermediate Intensive English I students of the Foreign Language department at the University of El Salvador - Chinchilla Maravilla, Mario Ernesto; Murga Olmos, Ruth Noemí; Sánchez Gochez, Abner Stalyn (2024)
The leading objective of this study was to show the effects that ludic activities have as a motivational strategy to evolve oral production of Intermediate Intensive English I students of the Foreign Language Department at the University of El Salvador. The research team reached the objective by using qualitative and quantitative guidelines. So, it led to a mixed method since the focal purpose was not only to describe students’ behaviors but to analyze the data on that basis. In order to gather all data basis, two groups were created; experimental and control group. Each group consisted of ten students and all students divided into the two groups following a random assignment method. A teacher was assigned to both groups in order to make sure both groups received the same level of motivation and there were no other variables on regards the teaching technique. However, ludic activities were applied in one group while the other group received no treatment. This article provided with a clear idea and overview of the research project